(untitled) (International Journal of Nursing Education, 2019)
Clinical simulation models have long been employed to teach clinical skills. The usage promotes satisfaction and confidence in learning among nursing students to learn the clinical skills. The study aimed to investigate the undergraduate nursing students’ satisfaction and self-confidence in learning using the clinical simulation models. It also determined the relationship between student satisfaction with self-confidence in learning. This quantitative cross-sectional survey employed Student Satisfaction and Self-Confidence in Learning Scale from the National League for Nursing. The 118 samples were recruited using the stratified sampling method among all years of undergraduate nursing students in a Public University in Malaysia. Descriptive statistics was used to describe the samples and scores of Student Satisfaction and Self-Confidence in Learning. Spearmen correlation was employed to test the relationship between Student Satisfaction with Self-Confidence in Learning and significant level was determined at p less than .05. Hundred and eighteen respondents with the age ranged from 20 to 25 years (M = 21.73, SD = 1.19) were females (91%) and nine (8%) were males. The overall satisfaction was more than 3.5 (M = 3.89, SD = 0.54). The overall self-confidence was also high (M = 4.01, SD = 0.68). The Spearman correlation result showed that the two variables were weakly correlated, r (116) = 0.485, p = .000. The findings showed that undergraduate nursing student in this study conveyed a high satisfaction and self-confidence in learning using the clinical simulation models despite a weak correlation between the two variables (p < .05). It is crucial that the simulations be continuously used with the hope of improving their clinical practice. The result of this study is relevant in supporting the used of simulation models in nursing education. It is recommended that future studies to include qualitative method to provide rich data on nursing student’s experiences